Let,you have an equation=$a^2-2ab+b^2$

This can be written in two ways-

$$a^2-2ab+b^2\space \space \space \space \space \space \space \space \space \space \space \space \space \space \space b^2-2ab+a^2$$

And so,


And so $a=b$

But,this is not true clearly. Where is this going wrong?

Thanks for any help!

  • $\begingroup$ $(-x)^2 = x^2$. $\endgroup$ – Daniel Fischer May 9 '16 at 13:33
  • $\begingroup$ @DanielFischer $(-2)^2=(2)^2$... $\endgroup$ – tatan May 9 '16 at 13:34
  • 7
    $\begingroup$ I don't understand how you conclude $a=b$ here even with flawed reasoning. Can you clarify? $\endgroup$ – JessicaK May 9 '16 at 13:36
  • 1
    $\begingroup$ So..? The point is that $ x^2 = y^2 $ does not allow you to conclude that $ x = y $, there is also the possibility that $ x = -y $. $\endgroup$ – Starfall May 9 '16 at 13:37
  • 3
    $\begingroup$ @JessicaK - From $(a-b)^2=(b-a)^2$ he concluded - wrongly - that $a-b=b-a$, i.e. $2a=2b$... $\endgroup$ – Mauro ALLEGRANZA May 9 '16 at 13:39

You cannot conclude that $a=b$ just because $(a-b)^{2}=(b-a)^{2}$.

Try $a=2$ and $b= 5$.

The fact is that the statement $(a-b)^{2}=(b-a)^{2}$ is always true. Given two numbers $a$ and $b$, $b-a$ and $a-b$ only differ by a factor of $-1$, which disappears when we square the two differences.


$(a-b)^2=(b-a)^2$ is true.

But you missed

$(a-b)=\pm (b-a) $


The statement, $u^2 = v^2 \Rightarrow u=v, $ is not true.
The true statement is: $u^2 = v^2 \Rightarrow \sqrt{u^2} = \sqrt{v^2}$ $\Rightarrow$ $|u|=|v|. $
So that from $(a-b)^2=(b-a)^2$ you can deduce $|a-b|=|b-a|$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.